CALCULATION OF BAND STRUCTURE AND STIMULATED EMISSION SPECTRUM FOR TWO DIMENSIONAL PHOTONIC CRYSTAL - GOMULYA (NIM 10204015); Pembimbing : Dr. Rahmat Hidayat, WIDIANTA
Photonic crystal structure have a great concern in the last one decade as a structure to control light propagating in analogy with controlling electron/hole in semiconductor crystal. The presence of periodical structure built from variation of refractive index results in the band-gap formation for light propagation inside the structure. This thesis describes the theory for the calculation of band-gap structure, that is the dispersion relation and the photonic density of states based on Plane Wave Expansion Method. The calculation results were obtained by solving the eigenvalue problem numerically. The calculation was applied for alumina structure (which has been reported by K. Sakoda) and polymer structure. Eigenvectors for magnetic field obtained from the eigenvalue problem solutions were also used for calculating optical amplification in stimulated emission process inside the structure. The results might be useful for understanding the possibility of polymer photonic crystal applications and their characteristics as photopumped laser devices.